Macrophages Switch to an Osteo‐Modulatory Profile Upon RANKL Induction in a Medaka (Oryzias latipes) Osteoporosis Model. (1st October 2020) - Phan, Quang Tien; Liu, Ranran; Tan, Wen Hui; Imangali, Nurgul; Cheong, Benedict; Schartl, Manfred; Winkler, Christoph
ABSTRACT: In mammals, osteoclasts differentiate from macrophages in the monocyte lineage. Although many factors driving osteoclast formation are known, the detailed processes underlying precursor recruitment, differentiation, and interaction of macrophages with other cell types involved in bone remodeling are poorly understood. Using live imaging in a transgenic medaka osteoporosis model, where ectopic osteoclasts are induced by RANKL expression, we show that a subset of macrophages is recruited to bone matrix to physically interact with bone‐forming osteoblast progenitors. These macrophages subsequently differentiate into cathepsin K‐ ( ctsk‐ ) positive osteoclasts. One day later, other macrophages are recruited to clear dying osteoclasts from resorbed bone by phagocytosis. To better understand the molecular changes underlying these dynamic processes, we performed transcriptome profiling of activated macrophages upon RANKL induction. This revealed an upregulation of several bone‐related transcripts. Besides osteoclast markers, we unexpectedly also found expression of osteoblast‐promoting signals in activated macrophages, suggesting a possible non‐cell autonomous role in osteogenesis. Finally, we show that macrophage differentiation into osteoclasts is dependent on inflammatory signals. Medaka deficient for TNFα or treated with the TNFα‐inhibitor pentoxifylline exhibited impaired macrophage recruitment and osteoclast differentiation. These results show the involvement of inflammatory signals and the dynamics of a distinct subset of macrophages during osteoclast formation. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract : Using live imaging in a medaka fish osteoporosis model, we report the dynamic recruitment of macrophages to bone matrix, their close interaction with osteoblasts and subsequent differentiation into osteoclasts. These processes require TNFa and involve significant transcriptomic changes as activated macrophages switch from an immune to a bone‐modulatory signature. Based on this signature, we propose a non‐cell autonomous role of RANKL‐activated macrophages in promoting cartilage and bone formation to achieve bone homeostasis.